Factors associated with adaptation to Klinefelter syndrome: The experience of adolescents and adults. Issue 1 (January 2015) - Turriff, Amy; Levy, Howard P.; Biesecker, Barbara
Highlights We report correlates of adaptation to XXY using a newly published adaptation scale. Participants reported significant negative consequences of living with XXY. Use of problem-focused coping strategies was positively correlated with adaptation. Age was negatively correlated with adaptation. Facilitating effective coping may improve adaptation among individuals with XXY.